IMPLEMENTATION OF EARLY CHILDREN'S CHARACTER EDUCATION THROUGH CONGKLAK GAMES FOR CHILDREN AGED 5-6 YEARS AT AISYIYAH KINDERGARTEN BUSTANUL ATHFAL 5 SAMARINDA SEBARANG - Ali, Suriani; Liana, Heppy; Aslina, Yeni (BEduManagers Journal : Borneo Educational Management and Research Journal, 2024)
This research aims to implement early childhood character education through the congklak game for children aged 5 - 6 years at the Aisyiyah Bustanul Atfhal 5 Samarinda Seberang kindergarten. The method used in this research is qualitative research. Qualitative research is a research method based on positivism or interpretive philosophy, used to examine the condition of natural objects, where the researcher is the key instrument. Data collection techniques include observation, interviews and documentation. Test the validity of the data using triangulation techniques. The research subjects in this study were 6 students of Aisyiyah Bustanul Atfhal 5 Kindergarten. Based on the data obtained from the research results, it shows that the implementation of character education through the congklak game for early childhood at the Aisyiyah Bustanul Atfhal 5 Samarinda Seberang Kindergarten achieved the character of religious, honest, cooperative, disciplined, responsible development according to expectations after going through three assessments according to researcher analysis. Efforts are made by educators to strengthen children's character by using congklak game media through habituation, continuous example by applying congklak play to children by including in the learning plan to play congklak twice a week during the research. This is an effort to make it easier for educators to implement children's character education. In this way, educators can assess children's character of honesty, patience, responsibility, and discipline through playing congklak